The climate risk initiatives of the Campinas city - Muniz, Sônia Regina Barreto; Domingues, Thais Martins; Paula, Maria Eunice Pereira de; Sugahara, Cibele Roberta; Benedicto, Samuel Carvalho De (Technical and Scientific Journal Green Cities, 2025)
Climate change has been the greatest problem faced by the world, it has provoked a diversity of loses to the planet and to the life on earth, this is majorly due to the anthropic actions in nature. For this reason, it is necessary to develop public policies and actions to face the environmental damage caused by climate change. The objective of this study is to analyze the climate risk actions taken by the city of Campinas/ SP having the Climate Action Local Plan (Plano Local de Ação Climática, PLAC in portuguese) as basis, to showcase the contributions it offers towards the achievement to the Sustainable Development Goal (SDG) number 13 – take urgent action to combat climate change and its impacts. The method employed was descriptive qualitative research, based on documents and case studies. Climate change reports were used to obtain data on the matter. As a result, it was concluded that Campinas is involved in public strategies of climate risk since 2013. With the development of PLAC, Campinas accepted the goal of reducing in 35% the greenhouse gas emissions up to 2040. The PLAC counts with five strategic axes aligned to the achievement of the SGDs, including actions already happening such as the monitoring of irregular waste. Campinas has great challenges to respond to the climate risk, such as to become a resilient city to extreme events, and an integrated and inclusive city.
Keywords: Climate change; Sustainable Development Goal; Local Climate Action Plan